Active polylactic acid film incorporated with green tea extract: Development, characterization and effectiveness - Martins, Cristiana (2018)
A new antioxidant active packaging film has been developed based on polylactic acid (PLA) in which green tea extract (GTE) has been immobilized by extrusion. Two GTE concentrations were tested, 1% (w/w) and 2% (w/w). Four GT samples were compared regarding their antioxidant capacity (by DPPH radical scavenging method and beta-carotene bleaching method), total phenolics content (TPC) and total flavonoids content (TFC). The commercial GTE presented with highest antioxidant capacity by the DPPH radical assay (EC50 = 0.12 +/- 0.00 mg/mL) and the highest TPC (416 +/- 9.95 mg gallic acid equivalents (GAE)/g extract) and it was selected to be incorporated in the active film. Films were evaluated regarding their mechanical properties (e.g. tensile strength decreased 12% with the incorporation of GTE in the PLA matrix and strain at break increased 9.6 and 36% with the addition of 1 and 2% of GTE) and water vapour transmission rates (water vapour barrier properties improved with the addition of higher amounts of GTE).The study of the effectiveness of PLA/GTE films against lipid oxidation was performed by the following methods: peroxide value, p-anisidine value, thiobarbituric acid reactive substances (TSARS) assay and hexanal monitoring, after packaging smoked salmon slices during different storage times (0, 7, 15, 30, 45 and 60 days). The results showed that the incorporation of GTE in the PLA films protects the smoked salmon from lipid oxidation in the different storage times tested. However, additional studies should be performed to better understand the GTE mechanism of action as the results suggest a pro-oxidant effect of PLA/GTE 2% after 60 days of storage and to evaluate the potential antimicrobial activity of active films.